2002
DOI: 10.1034/j.1399-6576.2003.470114.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of granisetron and granisetron plus dexamethasone for the prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy

Abstract: The combination (granisetron plus dexamethasone) further increases the chance of complete response than granisetron alone. Therefore, the combination might be considered clinically relevant in a high risk setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…4 Several previous studies have demonstrated that combination antiemetics were superior to individual drugs for the prophylactic prevention of PONV. [17][18][19][20][21] The results from this study are consistent with the previous findings. Johns et al demonstrated that the use of granisetron 1 mg iv and cyclizine 50 mg iv was associated with a higher efficacy compared with an individual antiemetic in patients undergoing ambulatory surgery.…”
Section: Discussionsupporting
confidence: 83%
“…4 Several previous studies have demonstrated that combination antiemetics were superior to individual drugs for the prophylactic prevention of PONV. [17][18][19][20][21] The results from this study are consistent with the previous findings. Johns et al demonstrated that the use of granisetron 1 mg iv and cyclizine 50 mg iv was associated with a higher efficacy compared with an individual antiemetic in patients undergoing ambulatory surgery.…”
Section: Discussionsupporting
confidence: 83%
“…Combination antiemetic therapy with serotonin antagonists (granisetron, ondansetron, tropisetron) plus dexamethasone, metoclopramide, or droperidol is known to be highly effective in preventing PONV [2,13,[31][32][33][34]. We did not use this combination therapy in the current study because there was no need to apply PCA, including opioids.…”
Section: Discussionmentioning
confidence: 81%
“…However, because of the multifactorial origin of PONV, none of the currently available antiemetics is fully effective in all patients. At present, when antiemetics of different pharmacological classes are available, it is possible to combine them and provide better control of PONV without producing additional side effects [17].Dexamethasone has been used as an antiemetic for more than 20 years in patients receiving chemotherapy [15], with limited side effects [1], and has also been reported to decrease PONV when added to the antiemetic regimen [4,6]. Recently, a combination of ondansetron and dexamethasone has been shown to be a highly effective prophylactic measure in patients undergoing laparoscopic cholecystectomy [6].…”
mentioning
confidence: 99%